Historical networks in the book trade - Feely, Catherine,Hinks, John (Routledge, 2017)
1. Introduction: beyond metaphor : a personal view of historical networks in the book trade / John Hinks – 2. Book trade networks and community contexts / John Feather – 3. Revealing and mapping networks : potential opportunities and pitfalls for book trade history / Steve Conway – 4. History, histories and book trade networks : an exploratory agent-based model / Edmund Chattoe-Brown and Simone Gabbriellini – 5. The book as movable property in England in the early Middle Ages / Elaine Treharne – 6. Minding their F's and Q's : Shakespeare and the Fleet Street syndicate 1630-32 / Jennifer M. Young – 7. The dissemination of political pamphlets in local towns : a comparison between late seventeenth-century Utrecht and Exeter / Roeland Harms – 8. Early book trade networks in Nottinghamshire and Derbyshire / Maureen Bell – 9. A hotbed of hawkers : Muneville-le-Bingard and the itinerant book trade in Northern France during the Ancien Regime / Ian Maxted – 10. The role of the Sydney Gazette in the creation of Australia in the Scottish public sphere / M.H. Beals – 11. Copyright law, transnational book trade, and the counter-discourse of the global in the Belgian market of cheap reprints / Alberto Gabriele – 12. Karl Marx's Capital and transatlantic radical book-trade networks in the early twentieth century / Catherine Feely.
10.4324/9781315636788
Keywords: Book industries and trade; Book industries and trade; History; 2; th century; Electronic books; Book industries and trade; History; 15th century; Book industries and trade; History; 20th century; BUSINESS & ECONOMICS; Commerce; bisacsh; BUSINESS & ECONOMICS; Marketing; General; bisacsh; BUSINESS & ECONOMICS; Sales & Selling; General; bisacsh; LITERARY CRITICISM / Books & Reading; bisacsh; HISTORY / Social History; bisacsh